P2Y1 Purinergic Receptor Contributes to Remifentanil-Induced Cold Hyperalgesia via Transient Receptor Potential Melastatin 8–Dependent Regulation of N-methyl-d-aspartate Receptor Phosphorylation in Dorsal Root Ganglion. (23rd June 2021) - Su, Lin; Bai, Xiaoqing; Niu, Tongxiang; Zhuang, Xinqi; Dong, Beibei; Li, Yize; Yu, Yonghao; Wang, Guolin
Abstract : BACKGROUND: Remifentanil can induce postinfusion cold hyperalgesia. N -methyl-d -aspartate receptor (NMDAR) activation and upregulation of transient receptor potential melastatin 8 (TRPM8) membrane trafficking in dorsal root ganglion (DRG) are critical to cold hyperalgesia derived from neuropathic pain, and TRPM8 activation causes NMDAR-dependent cold response. Contribution of P2Y1 purinergic receptor (P2Y1R) activation in DRG to cold pain hypersensitivity and NMDAR activation induced by P2Y1R upregulation in neurons are also unraveled. This study explores whether P2Y1R contributes to remifentanil-induced cold hyperalgesia via TRPM8-dependent regulation of NMDAR phosphorylation in DRG. METHODS: Rats with remifentanil-induced cold hyperalgesia were injected with TRPM8 antagonist or P2Y1R antagonist at 10 minutes before remifentanil infusion. Cold hyperalgesia (paw lift number and withdrawal duration on cold plate) was measured at −24, 2, 6, 24, and 48 hours following remifentanil infusion. After the last behavioral test, P2Y1R expression, TRPM8 expression and membrane trafficking, and NMDAR subunit (NR1 and NR2B) expression and phosphorylation in DRG were detected by western blot, and colocalization of P2Y1R with TRPM8 was determined by double-labeling immunofluorescence. Two-way repeated measures analysis of variance (ANOVA) or 2 × 2 factorial design ANOVA with repeated measures was used to analyze behavioral data of cold hyperalgesia. One-way ANOVA followed by Bonferroni post hoc comparisons was used to analyze the data in western blot and immunofluorescence. RESULTS: Remifentanil infusion (1 μg·kg −1 ·min −1 for 60 minutes) induced cold hyperalgesia (hyperalgesia versus control, paw lift number and withdrawal duration on cold plate at 2–48 hours, P < .0001) with upregulated NR1 (hyperalgesia versus naive, 48 hours, mean ± standard deviation [SD], 114.00% ± 12.48% vs 41.75% ± 5.20%, P < .005) and NR2B subunits expression (104.13% ± 8.37% vs 24.63% ± 4.87%, P < .005), NR1 phosphorylation at Ser896 (91.88% ± 7.08% vs 52.00% ± 7.31%, P < .005) and NR2B phosphorylation at Tyr1472 (115.75% ± 8.68% vs 59.75% ± 7.78%, P < .005), TRPM8 expression (115.38% ± 9.27% vs 40.50% ± 4.07%, P < .005) and membrane trafficking (112.88% ± 5.62% vs 48.88% ± 6.49%, P < .005), and P2Y1R expression (128.25% ± 14.86% vs 45.13% ± 7.97%, P < .005) in DRG. Both TRPM8 and P2Y1R antagonists attenuated remifentanil-induced cold hyperalgesia and downregulated increased NR1 and NR2B expression and phosphorylation induced by remifentanil (remifentanil + RQ-00203078 versus remifentanil + saline, NR1 phosphorylation, 69.38% ± 3.66% vs 92.13% ± 4.85%; NR2B phosphorylation, 72.25% ± 6.43% vs 111.75% ± 11.00%, P < .0001). NMDAR activation abolished inhibition of TRPM8 and P2Y1R antagonists on remifentanil-induced cold hyperalgesia. P2Y1R antagonist inhibited remifentanil-evoked elevations in TRPM8 expression and membrane trafficking and P2Y1R-TRPM8 coexpression (remifentanil + 2'-deoxy-N 6 -methyl adenosine 3', 5'-diphosphate [MRS2179] versus remifentanil + saline, coexpression, 8.33% ± 1.33% vs 22.19% ± 2.15%, P < .0001). CONCLUSIONS: Attenuation of remifentanil-induced cold hyperalgesia by P2Y1R inhibition is attributed to downregulations in NMDAR expression and phosphorylation via diminishing TRPM8 expression and membrane trafficking in DRG.